Selectable multiwavelength thulium-doped fiber laser based on parallel Lyot filter - Jamalus M.S.K.; Sulaiman A.H.; Abdullah F.; Zulkifli N.; Alresheedi M.T.; Mahdi M.A.; Yusoff N.M. (Academic Press Inc., 2023)
Fibers; Microcomputers; Polarization; Pumping (laser); Thulium; Intensity-dependent; Intensity-dependent loss; Laser-based; Loss mechanisms; Lyot filters; Multi wavelength fiber laser; Polarization controllers; Thulium doped fiber laser; Thulium-doped fibers; Wavelength spacing; Fiber lasers